"Um estudo sobre a contribuição dos sistemas de inteligência de negócios na gestão econômico-financeira das empresas" - Mantovani, Flavio Roberto (2005)
The purpose of this dissertation is the study about the contribution of the Business Intelligence Systems to the economical and financial management. The study is justified for considering the use of this technology, as an agent of organizational changes, bringing to the economical and financials manager new perspectives and better understanding of the entire business, qualifying them to act as partner, in strategic decisions for the company. Initially, we made a revision on the academic and specialized literature about Organization, Managerial Accounting, Economical and Financial Management and Information Technology approaching the technology of Business Intelligent Systems, the various components of its architecture and some functionalities of its application. The theoretical foundation and the field research performed in 11 companies, which Business Intelligence Systems were implemented, have supported the arguments to answer the problem of this research. The results obtained through out the bibliographical researches and the survey of this work, brought up the conclusion that the use of Business Intelligence tolls, can bring concrete contributions for the economical and financial management, such as: profitability evaluation; improvement in the quality level of the information and reports; speed up the time of reports generation, among others. It was also verified, that ad-hocs analysis using OLAP On line analytical processing - technology showed little contribution to the economical and financial management